Fakulta architektury, TU Dresden - Výška, Filip; Výška Filip (České vysoké učení technické v Praze, 2017)
Předmětem bakalářské práce je Fakulta architektury Technické univerzity v Drážďanech. Kromě funkce školy se v budově nachází kavárna a výstavní prostor s terasou. Budova je umístěna mezi přednáškovou budovu a Stavební fakultu a vytváří bránu do univerzitního kampusu.

The subject of the bachelor's thesis is the building of a Faculty of architecture of Technical university in Dresden. Besides its main educational function, the building is open to public with café and exposition space with a terasse. The building is situated in a corridor between seminary building and Faculty of Civil engineering and presents a gate to the university campus.
Faculty of Architecture, TU Dresden
Keywords: Fakulta architektury,Technická univerzita v Drážďanech; Faculty of architecture,Technical University in Dresden